Surgical management for ankle arthropathy in patients with hemophilia and other congenital coagulation disorders - Ricardo Rodríguez Ciodaro; Claudia Caicedo Donoso; María Helena Solano-Trujillo (Journal of the Foot & Ankle, 2023)
Objective: Compare the surgical treatment options available in our institution and the postoperative outcomes during follow-up. Additionally, assess patient’s perception of their condition and its progression. Methods: This descriptive observational study is a case series with a narrative literature review. All patients who met the inclusion and exclusion criteria and received surgical management for ankle arthropathy due to ankle hemarthrosis between 1999 and 2022 at Hospital San José in Bogotá were included. A perception survey was conducted via teleconsultation to evaluate pain control, functional impact, and capacity for daily activities. Results: Fifteen patients were included in the study, 13 male (86.7%). The mean age at the time of surgical intervention was 33 years (range 25–68). Among the patients, eight (53.3%) were diagnosed with Hemophilia A, four (26.7%) with Hemophilia B, two with Von Willebrand disease (13.3%), and one (6.7%) with Factor VII deficiency. The most common surgical intervention was ankle arthroscopy, with nine cases (50%). No infectious or intraoperative complications were documented, but one case of Hemophilic Pseudotumor developed late. The mean follow-up time was 87.7 months (IQR 60–105, SD 56.17). All patients reported improved pain and resumed their daily activities after the surgical intervention. Conclusion: Surgical management, regardless of the technique used (joint preservation or sacrifice), had a positive impact on patients by reducing pain after conservative management failure and allowing them to regain their daily activities, improving their quality of life. Level of Evidence IV; Therapeutic studies - investigating the results of treatment; Case series.